Charm Production in Antiproton-Proton Annihilation - Haidenbauer, J.; Krein, Gastão Inácio [UNESP] (Springer Wien, 2011)
We study the production of charmed mesons (D) and baryons (Lambda(c)) in antiproton- proton ((p) over barp) annihilation close to their respective production thresholds. The elementary charm production process is described by either baryon/ meson exchange or by quark/ gluon dynamics. Effects of the interactions in the initial and final states are taken into account rigorously. The calculations are performed in close analogy to our earlier study on (p) over bar -> (Lambda) over bar Lambda and (p) over barp (K) over bar K by connecting the processes via SU(4) flavor symmetry. Our predictions for the (Lambda) over bar (c)Lambda(c) production cross section are in the order of 1 to 7 mb, i. e. a factor of around 10-70 smaller than the corresponding cross sections for (Lambda) over bar Lambda However, they are 100 to 1000 times larger than predictions of other model calculations in the literature. on the other hand, the resulting cross sections for (D) over barD production are found to be in the order of 10(-2) - 10(-1)mu b and they turned out to be comparable to those obtained in other studies.